Consider that the point-slope form suggests that the equation of a straight line having slope 'm' and passing through a point, is given by,
![y-y_1=m\cdot(x-x_1)](https://img.qammunity.org/2023/formulas/mathematics/college/a2xqdh1ypfoabwyuxg9yhz2k40nj75jyd3.png)
Given that the slope of the line is 0,
![m=0](https://img.qammunity.org/2023/formulas/mathematics/high-school/hp9nuzue9owdf40hqdr22fz2gdi678idi4.png)
Also, the line passes through the point,
![(x_1,y_1)=(-1,-2)](https://img.qammunity.org/2023/formulas/mathematics/college/njn2tnhrzvobahdyv9siu9nbcsol8l82vf.png)
Substitute the values,
![\begin{gathered} y-(-2)=0\cdot(x-(-1)) \\ y+2=0 \\ y=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/8jwc0adiwopvb1dpsioxjclyhz384foi2l.png)
Thus, the equation of the line having slope 0 and passing through (-1,-2) is obtained as,
![y=-2](https://img.qammunity.org/2023/formulas/mathematics/high-school/tcn3iys8rd82ithvwo5zbctm5hqvvqtks0.png)